Selection of Socially Responsible Portfolios Using Hedonic Prices - Bilbao Terol, Amelia; Arenas-Parra, Mar; Cañal-Fernández, Verónica; Bilbao, Cecilia (2013)
This paper presents a novel framework for selecting socially responsible investment (SRI) portfolios. The Hedonic Price Method (HPM) is applied to obtain an evaluation of SRI criteria that is integrated into a multi-objective mathematical programming model. The HPM breaks away from the traditional view that goods are the direct object of utility; on the contrary, it assumes that utility is derived from the properties or characteristics of the goods themselves. As far as the investment decision is concerned, we assume that socially responsible investmentmutual funds (SRI funds) constitute heterogeneous goods. Our approach allows us to obtain a portfolio, the financial performance of which is similar to that which the investor would have reached if he or she had not taken into account social, ethical, and environmental considerations when making his or her investment decisions. This is achieved by designing a two-stage multi-objective mathematical programming procedure. In the first stage, we achieve the maximum level of financial satisfaction that the investor can receive. In the second stage, the portfolio with the best financial–social behavior is built. For the purpose of this second stage, the first stage portfolio is used as a benchmark for the financial performance of a socially responsible portfolio. To apply this methodology, we use portfolios composed of socially responsible and conventional mutual funds domiciled in Spain.
Keywords: Certainty equivalent; Conditional value-at-risk; Variance; Hedonic prices; Multi-objective programming; mutual funds; Portfolio Selection; Socially Responsible Investment